KESIAPAN KARYAWAN ADMINISTRASI YANG TERKENA ROTASIKERJA PADA BAGIAN PEMASARAN - Arundati Shinta, Nurhadi, T.A. Prapancha Harry, dan Siti Mahmudah (Jurnal Psikologi, 2016)
Objective of this reserach is to know employee’s readiness whom experiencing job rotation from administration into selling division. Their readiness (knowledge and skill) were important since their new position was very different from the previous position. Nine employees participated in this research. They were from an organization which was nearly ruin because of management changes. In order to continue to exist, those employees had been rotated into the selling devition. This research revealed that the employee’s previous knowledge and skill were less appropriate to the selling division requirement. They had difficulties in public speaking and information technology. They were also more likely ashamed with the organization although their work tenure was more than 20 years. This was shown from their answer that they had limited knowledege about the positive aspects of the organiation. At the discussion session, we explain that this research result could be a good base for planning and organiziang job rotation. Beside that the middle age employees should be taken care when they experience job rotation. Management should organize several trainings which emphasize on repetitive tasks. That kind of training will more likely to stimulate cognitive condition much better.